Evaluasi Kelengkapan Administratif dan Farmasetis Resep di Poliklinik Anak Rumah Sakit Karanggede Sisma Medika Boyolali - Paulina Maya Octasari; Patriana Agustin Windasari (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2022)
Prescription screening is one of the pharmaceutical services carried out by reviewing prescriptions according to administrative, pharmaceutical and clinical requirements. Administrative and pharmaceutical requirements ensure the legality of prescriptions, correct identification and successful treatment of patients. The purpose of this study was to evaluate the administrative and pharmaceutical completeness of prescriptions at the Children's Polyclinic Karanggede Sisma Medika Hospital Boyolali. This research was carried out in an observational descriptive manner with retrospective data from prescriptions at the Children's Polyclinic at Karanggede Sisma Medika Boyolali Hospital for the period July – September 2021, with a total sample of 215 prescription sheets. The complete administrative prescription data includes the patient's name, medical record number, gender, date of birth, doctor's name, doctor's initials and date of prescription. Complete prescription pharmaceutical data include the name of the drug, the dosage form, the strength of the preparation, the dosage unit, the amount of the drug, the rules for use and how to use it. The data were analyzed quantitatively to determine the percentage of administrative completeness, pharmaceutical completeness, and both. The study was conducted with 215 prescriptions. The results of this study showed that 43.72% of prescriptions were administratively complete which consisted of 100% of the patient's names. As many as 60% are complete pharmaceutically consisting of the name of the drug, the form of the drug and the amount of the drug by 100%, and 28.37% complete both.